Removal of copper by Azolla filiculoides and Lemna minor: phytoremediation potential, adsorption kinetics and isotherms - Israa Abdulwahab Al-Baldawi; Safaa Rasheed Yasin; Salwa Shamran Jasim; Siti Rozaimah Sheikh Abdullah; Asia Fadhile Almansoory; Nur 'Izzati Ismail (Heliyon, 2022)
Phytoremediation is an eco-friendly biotechnology with low costs. The removal of copper (Cu) from polluted water by the two floating plant species Azolla filiculoides and Lemna minor was observed and recorded. Plants were exposed to different Cu (II) concentration (0.25–1.00 mg/L) and sampling time (Days 0, 1, 2, 5 and 7). Both plants can remove Cu at 1.00 mg Cu/L water, with the highest removal rates of 100% for A. filiculoides and 74% for L. minor on the fifth day of exposure. At the end of the exposure period (Day 7), the growth of A. filiculoides exposed to 1.00 mg Cu/L was inhibited by Cu, but the structure of the inner cells of A. filiculoides was well organized as compared to the initial treatment period. Regarding L. minor, Cu at 1.00 mg/L negatively impacted both the growth and morphology (shrinking of its inner structure) of this plant. This is due to the higher accumulation of Cu in L. minor (2.86 mg/g) than in A. filiculoides (1.49 mg/g). Additionally, the rate of Cu removal per dry mass of plant fitted a pseudo-second order model for both plants, whereas the adsorption equilibrium data fitted the Freundlich isotherm, indicating that Cu adsorption occurs in multiple layers. Based on the results, both species can be applied in the phytoremediation of Cu-polluted water.